2020
DOI: 10.3390/su12030940
|View full text |Cite
|
Sign up to set email alerts
|

Employee Commitment Matters for CSR Practice, Reputation and Corporate Brand Performance—European Model

Abstract: So far, there have been no studies that explore how employee brand commitment moderates CSR practice outcomes. Employee brand commitment is often claimed as a focal input and output of the CSR. So, it means that it shapes CSR conditions. Then, it is a moderator. This study aims to verify it. Besides, commitment exists in many forms and can be achieved in many ways. Hence the question, if employees are committed to the brand, then how does it affect the outcomes of social responsibility practices such as corpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 81 publications
1
29
0
1
Order By: Relevance
“…Organizations that develop strategies, policies, and practices related to social responsibility have higher levels of perceived reputation (Verčič & Orić, 2018). Javed et al (2020); Aksak et al, (2016); Vishwanathan et al (2020); Rehman et al (2020); and Kucharska (2020) found empirical evidence that CSR disclosure will be able to have a positive impact on the corporate reputation. Meanwhile, Pham & Tran (2020) found that company reputation was able to mediate the relationship between CSR and company performance.…”
Section: Perceived Csr On Corporate Reputationmentioning
confidence: 99%
“…Organizations that develop strategies, policies, and practices related to social responsibility have higher levels of perceived reputation (Verčič & Orić, 2018). Javed et al (2020); Aksak et al, (2016); Vishwanathan et al (2020); Rehman et al (2020); and Kucharska (2020) found empirical evidence that CSR disclosure will be able to have a positive impact on the corporate reputation. Meanwhile, Pham & Tran (2020) found that company reputation was able to mediate the relationship between CSR and company performance.…”
Section: Perceived Csr On Corporate Reputationmentioning
confidence: 99%
“…31 A company may charge premium if it possesses competitive advantage in terms of superior brand reputation. 32 A well-reputed company attracts more qualified personnel and that, in turn, brings about valuable transactions from customers. 31 Corporate reputation plays a vital role in the success and in being a profitable brand in almost every industry and business.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…In this way, firms can develop true and sustainable presence including the sustainable bionetwork for the organization. 32 However, the image of a company is consolidated only if the identity is well founded. Moreover, it is not easy to build image of a brand in the market.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Stakeholders, in particular consumers (Lee & Marshall, 2013) and workers (Kucharska, 2020;Mella & Gazzola, 2015, Gazzola, 2018, consider reputation as a central element for evaluating companies (Tetrault Sirsly & Lvina, 2019;Gray & Ballmer, 2006;Rhee & Haunschild, 2006). According to Fombrun (1996) -corporate reputation is a perceptual representation of a company's past actions and future prospects that describe the firm's overall appeal to all of its key constituents when compared with other leading rivals‖.…”
Section: Corporate Reputation and Csrmentioning
confidence: 99%